2022
DOI: 10.3390/act11090243
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Radially Closable Tubular Origami Structure (RC-ori) for Valves

Abstract: Cylindrical Kresling origami structures are often used in engineering fields due to their axial stretchability, tunable stiffness, and bistability, while their radial closability is rarely mentioned to date. This feature enables a valvelike function, which inspired this study to develop a new origami-based valve. With the unique one-piece structure of origami, the valve requires fewer parts, which can improve its tightness and reduce the cleaning process. These advantages meet the requirements of sanitary valv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Filipov assembled various Miura origami tubes to create a metamaterial that can be deployed, stiffened, and tuned 18 . A radially closable structure (RC-ori), a modified form of Kresling origami with crease lines, has also been proposed 19 . Adding incisions on the creases of Kresling origami significantly reduced the bistable actuation force during compression 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Filipov assembled various Miura origami tubes to create a metamaterial that can be deployed, stiffened, and tuned 18 . A radially closable structure (RC-ori), a modified form of Kresling origami with crease lines, has also been proposed 19 . Adding incisions on the creases of Kresling origami significantly reduced the bistable actuation force during compression 20 .…”
Section: Introductionmentioning
confidence: 99%
“…[32,33] The potential of the pattern extends even to the fields of energy absorption [34,35] and harvesting, [36,37] and it has been found that geometrical configuration can enhance the design and performance of the structure. [38,39] Other applications span pneumatic and wave manipulators, [40,41] mechanical binary switches, [42] helical antennas, [43] design and control, [44,45] biometric identity recognition, [46] multimodal locomotion, [47] electricity generator, [48] enhanced vibration isolation, [49] origami-based valve, [50] and origami springs. [51] Except the Kresling origami, an additional multistable (noninflatable) twisting meta-structure was proposed by Pan et al [52] based on the first buckling mode shape of a clamped-pinned beam.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [20], the tristable property of the Kresling origami was proposed on the cylindrical and conical structures. Ye et al [21] optimized the Kresling origami to obtain the radial closability, the valley creases within the unit cells are not connected to the vertices of the top (bottom) polygon. Liu et al [22] integrated the concept of Kirigami to split the unit cells of the Kresling origami, realizing rigid foldability, bistability, opposite chirality, and etc.…”
Section: Introductionmentioning
confidence: 99%